High HTLV-1 proviral load predates and predicts HTLV-1-associated disease: literature review and the London experience - Taylor,GP; Evans,W; Rosadas,C (Pathogens, 2024)
Human T cell lymphotropic virus type 1 (HTLV-1) is a retrovirus that infects lymphocytes and causes severe diseases. HTLV-1 proviral load (PVL), i.e., the number of host cells that carry HTLV-1 proviral DNA integrated into their genome, can be measured in peripheral blood mononuclear cells (PBMCs) using quantitative polymerase chain reaction. In this narrative review, we discuss the usefulness of HTLV-1 PVL quantification and share our experience acquired during more than 30 years of follow-up of people living with HTLV-1 in the UK. Patients with HTLV-1-associated myelopathy have higher PVL than those with asymptomatic infection. This is consistent across studies in different countries. High PVL predates symptom onset for both inflammatory and proliferative diseases. High PVL is essential but not sufficient for the development of HTLV-1-associated diseases. Therefore, PVL quantification can be used to support the care of people living with HTLV-1 by identifying those most at risk of HTLV-1-associated diseases.